Nonthermal plasma--A tool for decontamination and disinfection - Scholtz, Vladimir; Pazlarova, Jarmila; Souskova, Hana; Khun, Josef; Julak, Jaroslav (Biotechnology advances, 2015)
By definition, the nonthermal plasma (NTP) is partially ionized gas where the energy is stored mostly in the free electrons and the overall temperature remains low. NTP is widely used for many years in various applications such as low-temperature plasma chemistry, removal of gaseous pollutants, in gas-discharge lamps or surface modification. However, during the last ten years, NTP usage expanded to new biological areas of application like plasma microorganisms' inactivation, ready-to-eat food preparation, biofilm degradation or in healthcare, where it seems to be important for the treatment of cancer cells and in the initiation of apoptosis, prion inactivation, prevention of nosocomial infections or in the therapy of infected wounds. These areas are presented and documented in this paper as a review of representative publications.
Keywords: Food safety; Nonthermal plasma; dezinfekce; Humans; plazmové plyny; obaly potravin; Water cleaning; Biofilm inactivation; Medical application; Disinfection; lidé; Biotechnology application; Food Packaging; čištění vody; dekontaminace; Decontamination; Water Purification; Neoplasms; nádory; Microbicidal effect; Plasma Gases; Microbial decontamination